An investigation of heavy metals pollution in Sebakwe River Kwekwe, Zimbabwe - Chibanda, Maryleen (Midlands State University, 2019)
Pollution of aquatic ecosystems with heavy metals is now of global concern due to their effects on human health and persistence in the environment. The study was carried out to determine the heavy metal pollution in Sebakwe River Kwekwe, Zimbabwe. To provide information on heavy metals chromium, lead, copper, magnesium and iron concentrations in water and sediments, samples were collected at five sites in January 2019 and in February 2019. The samples were acid digested and analysed with an atomic absorption spectrophotometer (AAS). The results showed that all studied metals were present in water and sediment samples and the mean concentrations of all metals occurred in the order Pb> Mg > Fe > Cu > Cr for both samples. There were significant differences in levels of Pb, Cr and Cu in water and Pb, Cr, Mg and Fe in sediments among the 5 sites. Correlation analysis showed a positive relationship between heavy metals in water and those in sediments. The highest contamination degree of the sediment was observed at site 3, the point of sewage discharge and lowest at site 5. Pollution load index (PLI) showed that sediments were uncontaminated to moderately contaminated. Levels of Pb were above permissible limits of SAZ and WHO in water posing a potential health hazard to the aquatic organisms and human inhabitants of the area that use this water resource directly for domestic or agricultural purposes. The results of metal concentration in water and sediments from this study are important as a baseline for future monitoring studies.